About the future of the Church. Analysis of selected ecclesiological debate: Analysis of selected ecclesiological debate - Artemiuk, Przemysław (Studia Teologiczne Białystok Drohiczyn Łomża, 2024)
The aim of the article is, firstly, to present the ecclesiological debate regarding the future of the Catholic Church; secondly, presenting it against a historical and theological background; thirdly, drawing conclusions regarding the studied issues. In the first part of the article, the author presents the thought of Chantal Delsol. In the second part, he presents Tomáš Halík's view on this issue. The third part is a summary and evaluation. The conducted research allows for the following conclusions to be drawn: the change in Catholicism does not mean the end of the Church, but the disintegration of the current imaginary in which the essence of faith remains unchanged; the situation of the Catholic Church is so serious that changes are needed, not only in the structures, but in the faith that requires deepening and renewal.